Why depolarization is hard: Evaluating attempts to decrease partisan animosity in America - Derek E. Holliday; Yphtach Lelkes; Sean J. Westwood (Proceedings of the National Academy of Sciences, 2025)
Affective polarization is a corrosive force in American politics. While numerous studies have developed interventions to reduce it, their capacity for creating lasting, large-scale change is unclear. This study comprehensively evaluates existing interventions through a meta-analysis of 77 treatments from 25 published studies and two large-scale experiments. Our meta-analysis reveals that the average effect of treatments on animosity is modest (a 5.4-point shift on a 101-point scale), and decays within two weeks. We experimentally test whether stacking multiple treatments in one sitting or repeating them over time as “booster shots” enhances their impact. We find no evidence that multiple or repeated exposures produce substantially larger or more durable reductions in partisan animosity. This reveals the uneven utility of these interventions. They serve as valuable tools for testing the psychological mechanisms of polarization, but our findings indicate they are not, on their own, a scalable solution for reducing societal-level conflict. We conclude that achieving lasting depolarization will likely require a shift in focus, moving beyond individual-level treatments to address the elite behaviors and structural incentives that fuel partisan conflict.